Impact of the "Looking after my health after cancer" peer-led active patient education program on cancer survivors and their caregivers: A qualitative study. - Ainhoa Ulibarri-Ochoa; Sheila Sánchez-Gómez; Estíbaliz Gamboa-Moreno; Irene Duo-Trecet; Lucia Garate-Echenique; Begoña Belarra-Tellechea; Lourdes Ochoa de Retana-García (PLoS ONE, 2023)
Background Cancer survival has doubled and is likely to continue increasing in the near future. Cancer survivors experience long-term adverse effects, with associated psychological changes, and often they have needs that are yet to be met. Recognizing the lack of continuity-of-care initiatives for cancer survivors and caregivers, Osakidetza Basque Health Service has started to implement through primary care a peer-led active patient education program called "Looking after my health after cancer". This study explores how cancer survivors and their caregivers rate the experience of participating in the program, to what extent the program helps them understand and address their unmet felt needs, and helps them improve their activation for self-care and self-management. Methods A qualitative exploratory phenomenological study was conducted using five focus groups: four with cancer survivors (n = 29) and caregivers (n = 2), and one with peer leaders (n = 7). Narrative content analysis was performed using the constant comparison method, facilitated by Atlas-ti software. Descriptive analysis of sociodemographic and clinical data was performed. The study was developed according to the Consolidated criteria for reporting qualitative research (COREQ) checklist. Results Five main themes emerged from the content analysis: 1) satisfaction with the program as a positive learning experience; 2) peer sharing and learning ("if they can, so can I"); 3) fears prior to attending the program; 4) becoming more aware of unmet felt needs and feeling understood in the "new normal"; and 5) a more positive view of their experience, helping them become active in self-care and empowered in the self-management of their condition. Conclusions The peer education program has shown to have a positive impact on cancer survivors and caregivers. It is necessary to design, implement and evaluate interventions of this type to address unmet felt needs during cancer survivorship and improve their quality of life.